Cathepsin B: Multiple roles in cancer. Issue 5 (26th March 2014) - Aggarwal, Neha; Sloane, Bonnie F.; Schilling, Oliver; Findeisen, Peter
<x xml:space="preserve">Abstract</x> Proteases, including intracellular proteases, play roles at many different stages of malignant progression. Our focus here is cathepsin B, a lysosomal cysteine cathepsin. High levels of cathepsin B are found in a wide variety of human cancers, levels that often induce secretion and association of cathepsin B with the tumor cell membrane. In experimental models, such as transgenic models of murine pancreatic and mammary carcinomas, causal roles for cathepsin B have been demonstrated in initiation, growth/tumor cell proliferation, angiogenesis, invasion, and metastasis. Tumor growth in transgenic models is promoted by cathepsin B in tumor‐associated cells, for example, tumor‐associated macrophages, as well as in tumor cells. In transgenic models, the absence of cathepsin B has been associated with enhanced apoptosis, yet cathepsin B also has been shown to contribute to apoptosis. Cathepsin B is part of a proteolytic pathway identified in xenograft models of human glioma; targeting only cathepsin B in these tumors is less effective than targeting cathepsin B in combination with other proteases or protease receptors. Understanding the mechanisms responsible for increased expression of cathepsin B in tumors and association of cathepsin B with tumor cell membranes is needed to determine whether targeting cathepsin B could be of therapeutic benefit.